The German Energy System: Analysis of Past, Present, and Future Developments - Edo, Great Iruoghene (Advanced Energy Conversion Materials, 2023)
The scientific and public debate centers on the specific policies that make up the energy transition policy, as well as issues surrounding how they interact and fit into the European context. The Federal Government of Germany came to a conclusion to change the existing structure of the country's energy supply system by ending nuclear energy conversion and strongly promoting the development of renewable energies. It is been seen that briefly after the Fukushima Daiichi nuclear disaster in Japan in 2011, it is seen the Federal Government of Germany came to a conclusion to change the existing structure of the country's energy supply system by ending nuclear energy conversion and strongly promoting the development of renewable energies. This paper aims at reviewing the past, present, and future of energy in Germany. It provides an overview of the historical trends of energy in Germany under energy use (kg of oil equivalent per capita), fossil fuel energy consumption (% of total), renewable energy development, and evolution of renewable energy patents. The requirements of such a system are not satisfied by policy approaches or recommendations that target short-term effects or that are perceptions of problems extrapolated from individual sectors. By collecting information from the literatures, it analyses current energy issues in Germany and the future of energy in Germany. This paper tends to bring to understanding the state of energy in Germany.